Agronomic performance of sunflower varieties as a function of plant populations - Ferreira, Bruno Gomes Candido; Kikuti, Hamilton; Kikuti, Ana Lúcia Pereira; Pereira, Carlos Eduardo (Revista de Ciências Agroveterinárias, 2023)
Sunflower is a plant that adapts to different soil and climatic conditions, being used for human and animal food, and ornamental purposes. The objective of this work was to evaluate the agronomic performance of sunflower varieties grown in different plant densities. A randomized complete block experimental design was used, in a 3x4 factorial, with 3 sunflower varieties (Embrapa 122, IAC Iarama, IAC Uruguay) and 4 plant populations (30, 45, 60 and 75 thousand plants per hectare), with 4 repetitions. Each plot consisted of 4 rows of plants with 5 meters in length and spacing of 0.70 m between rows of plants. At harvest were evaluated: plant height; stem diameter; capitulum size; one thousand achenes weight; number of capitulum. There was a significant effect of different sunflower varieties on plant height, capitulum diameter, number of small capitulum, number of normal capitulum, and total number of capitulum. There was also a significant effect of plant population on capitulum diameter, plant height, total number of capitulum and number of small capitulum. The interaction between varieties and population was significant only for the number of normal capitula and productivity. The ideal plant density for the agronomic performance of the sunflower crop depends on the variety used. The higher density of plants allows for greater productivity of the variety Embrapa 122.